Elaboración de un cortometraje publicitario para promover y difundir la feria de cerámica, en la parroquia La Victoria del cantón Pujilí provincia de Cotopaxi período 2016 - Azogue Yanchaliquin, Rubén Emilio (2016)
The current project has the finality to disseminate the importance to in pottery of the craft fair of ceramics, through an audiovisual proposal that allows establish a positive image that encourage the valorization of the culture of La Victoria Parish. In this project, it was applied different methods of investigation such as deductive, analytical scientific, descriptive, field and bibliographic methods; also it was applied the survey and interview techniques to craftsmen to recollect information necessary to this production. To produce the advertising short film was used all the information of the native people like experiences….